PERFORMANCE OF NON-CIVIL SERVANT GOVERNMENT EMPLOYEES (PPNPN) BASED ON WORK DISCIPLINE AND WORK MOTIVATION - Andrih, Andrih; Sudarijati, Sudarijati; Yulianingsih, Yulianingsih (Gema Kampus IISIP YAPIS Biak, 2025)
This study aims to analyze the influence of work discipline and work motivation on the performance of Non-Civil Servant Government Employees (PPNPN). The research methods used were quantitative descriptive and verifiable with a saturated sample of 76 respondents. Data analysis uses multiple regression, multiple correlation, coefficient of determination, and F test and t test. The results of the study show that partially and simultaneously work discipline and work motivation have a positive and significant influence on employee performance. Therefore, it is necessary to supervise work discipline more intensively and provide more work motivation, so that employee performance increases.